Heat shock protein 70-2 (HSP70-2) overexpression in breast cancer. Issue 1 (December 2016) - Jagadish, Nirmala; Agarwal, Sumit; Gupta, Namita; Fatima, Rukhsar; Devi, Sonika; Kumar, Vikash; Suri, Vaishali; Kumar, Rajive; Suri, Vitusha; Sadasukhi, Trilok; Gupta, Anju; Ansari, Abdul; et al.
Abstract Background Breast cancer is one of the leading cause of cancer-related deaths in women worldwide and increasing rapidly in developing countries. In the present study, we investigated the potential role and association of HSP70-2 with breast cancer. Methods HSP70-2 expression was examined in 154 tumor and 103 adjacent non-cancerous tissue (ANCT) specimens and breast cancer cell lines (MCF7, BT-474, SK-BR-3 and MDA-MB-231) by RT-PCR, quantitative-PCR, immunohistochemistry, Western blotting, flow cytometry and indirect immunofluorescence. Plasmid driven short hairpin RNA approach was employed to validate the role of HSP70-2 in cellular proliferation, senescence, migration, invasion and tumor growth. Further, we studied the effect of HSP70-2 protein ablation on signaling cascades involved in apoptosis, cell cycle and Epithelial-Mesenchymal-Transition both in culture as well as in-vivo human breast xenograft mouse model. Results HSP70-2 expression was detected in majority of breast cancer patients (83 %) irrespective of various histotypes, stages and grades. HSP70-2 expression was also observed in all breast cancer cells (BT-474, MCF7, MDA-MB-231 and SK-BR-3) used in this study. Depletion of HSP70-2 in MDA-MB-231 and MCF7 cells resulted in a significant reduction in cellular growth, motility, onset of apoptosis, senescence, cell cycle arrest as well as reduction of tumor growth in the xenograft model. At molecular level, down-regulation of HSP70-2 resulted in reduced expression of cyclins, cyclin dependent kinases, anti-apoptotic molecules and mesenchymal markers and enhanced expression of CDK inhibitors, caspases, pro-apoptotic molecules and epithelial markers. Conclusions HSP70-2 is over expressed in breast cancer patients and was involved in malignant properties of breast cancer. This suggests HSP70-2 may be potential candidate molecule for development of better breast cancer treatment.